PERLINDUNGAN HUKUM TERHADAP NASABAH KORBAN PENGGANDAAN KARTU ATM MENURUT UNDANG-UNDANG NOMOR 10 TAHUN 1998 TENTANG PERBANKAN (Studi Kasus pada Bank BRI Cabang Denpasar) - Ni Made Trisna Dewi; A.A Mas Adi Trinaya Dewi; Ni Luh Sri Mahendra Dewi (Jurnal Analisis Hukum, 2020)
Banks are business entities that collect funds from the public in the form of deposits and distribute them to the public in the form of loans and or other forms in order to improve the lives of the masses. The main function of Indonesian banks is as a collector and distributor of public funds. Protection of customers' funds in Indonesia is regulated in the Laws of the Republic of Indonesia Number 10 of 1998 concerning Banks. The increasing incidence of theft of bank customers' funds through the misuse of the ATM service system, reduced account balance has led to the need for further attention regarding how to guarantee the safety of use of ATMs and the prosecution of perpetrators of ATM duplication that can harm both the users of ATMs or the Bank itself. Based on this background, the problems that can be formulated to be discussed is : Are victims of ATM card duplication guaranteed refund by bank  and what is the procedure for refunding for victims of ATM card duplication.This paper uses a method with an empirical type of legal research, which is a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observationThe Conclusion if this research is Laws of the Republic of Indonesia Number 10 of 1998 concerning Banks. article 37B number (1) stated that:  “that the bank guarantees the public funds held at the bank concerned“. The following phrase of Article 37B stated that guarantee of bank customer deposits is carried out by a deposit insurance institution . Further arrangements regarding deposit insurance institutions are regulated in Laws of the Republic of Indonesia Number  10 of  2004 concerning  deposit insurance institutions .  the procedures begins by making a complaint by reporting through the BRI call center  or coming directly to nearest branch of Bank BRI to make a report about loss of funds due to victim of ATM duplication. settlement of complaints from customers is carried out entirely by the head office  of Bank BRI. After it is confirmed that the loss of funds is due to victim of ATM duplication,  Bank BRI will refund the victims' customers directly through a direct transfer to each customer's account